Chuva e banco de sementes em Floresta Estacional Semidecidual com diferentes históricos de uso do solo - Gorsani, Rodrigo Gomes (2019)
The seeds rain along the soil seeds bank composes a dynamic system which autochthonous and allochthonous propagules are integrated with variations from abiotic and biotic factors being the main sources of recruitment of new individuals during the secondary succession. In this sense, this study aimed to analyze the floristic composition of the seeds rain and the soil seeds bank, evaluating possible differences arising from different soil uses in a fragment of the Semideciduous Seasonal Forest in the city of Alegre-ES. The seeds bank was collected at the end of the seasons (rainy and dry) in 24 plots. In each plot, three samples were collected (totaling 72 samples), using a wooden frame (25 cm x 25 cm x 8 cm). These samples were transferred to plastic trays in a shade house with a shade cloth of 65% and the germination was evaluated for six months. The seeds rain was collected monthly, during a year, in 120 circular collectors with an area of 0,196 m² in the same plots. Subsequently, the sorting was done by separating the seeds from the other components and counting them in each area and month. The data of dominance, richness and diversity of the seeds bank and the seeds rain were compared between the areas with different soil use histories by the Kruskal-Wallis test. The Mann-Whitney test was used for the comparison of the seeds bank between stations. The floristic similarity of the seeds bank between the areas was analyzed based on the Bray-Curtis index, with UPGMA method, whereas for the seed rain the Jaccard index was used, as well as for the floristic relations between the seeds bank and the seeds rain, natural regeneration and adult vegetation by an NMDS. Data of canopy opening, slope, declivity and secondary data of soil physicochemical characterization were used to verify the correlation of seeds density per plot of soil seeds bank. In this mechanism, no differences between seasons were observed in any parameter and in between the areas only richness differed. In the seeds rain there was no difference in any parameter between areas. The floristic similarity between the seeds bank of the areas with different soil use histories was higher among forest - FLO and pasture - PAS (46%), and lower for the coffee area - CAF. Only the clay content had a strong negative correlation with the seeds density. The floristic similarity of the seeds rain was small, varying between 0.3 and 0.42, being close between all the areas. The NMDS revealed that there is more proximity between the FLO and PAS areas in all components of the vegetation analyzed and between each component with itself, besides the larger distance of the seeds bank in relation to the others. With these results it is observed that in spite of the different soil use histories of the areas and the consequent environmental changes, the areas have continued in secondary succession by sharing species and producing similar amounts of seeds.